Synthesis of nanoparticles composed of silver and silver chloride for a plasmonic photocatalyst using an extract from a weed Solidago altissima (goldenrod). (8th January 2016) - Kumar, Vemu Anil; Uchida, Takashi; Mizuki, Toru; Nakajima, Yoshikata; Katsube, Yoshihiro; Hanajiri, Tatsuro; Maekawa, Toru
Abstract: Phytosynthesis of nanomaterials is advantageous since it is economical, ecofriendly, and simple, and, what is more, in the synthetic protocols, nontoxic chemicals and biocompatible materials are used. Here, a green synthetic methodology of nanoparticles (NPs) composed of silver (Ag) and silver chloride (AgCl) NPs is developed using a leaf extract of Solidago altissima as a reducing agent for the first time. Utilization of a terrestrial weed for the synthesis of Ag and AgCl NPs is a novel environmentally friendly approach considering that no toxic chemicals, external halide source, or elaborate experimental procedures are included in the process. The optical properties and elemental compositions of as-synthesized Ag and AgCl NPs are well characterized, and the degradation of an organic dye, i.e., rhodamine B (RhB), is investigated using the Ag and AgCl NPs. We find that degradation of RhB is effectively achieved thanks to both surface plasmon resonance and semiconductor properties of Ag and AgCl NPs. The surface-enhanced Raman scattering and antibacterial activities are also examined. The present approach to the synthesis of NPs using a weed may encourage the utilization of hazardous plants for the creation of novel nanomaterials.